2002
DOI: 10.1071/rd02027
|View full text |Cite
|
Sign up to set email alerts
|

Expression of anti-Müllerian hormone mRNA during gonadal and follicular development in the brushtail possum (Trichosurus vulpecula)

Abstract: The ontogeny of anti-Müllerian hormone (AMH) gene expression in the brushtail possum during formation of the ovary and growth of follicles was examined using in situ hybridization. For comparative purposes, the expression pattern of AMH was also examined in the developing testis. In the female, AMH mRNA was observed in the ovary of 50% (3/6) of pouch young collected around the time of sexual differentiation of the gonad (Days 1-5): the signal was predominately localized to the inner-cortical and outer-medullar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
4
15
1
Order By: Relevance
“…The expression profiles of MIS in the adult human and monkey ovary are identical and comparable to that observed previously in other species (Bezard et al 1987, Uneo et al 1989a, Baarends et al 1995, Juengel et al 2002, Visser et al 2006. Table 1 compares the results of different studies on cellular localization of MIS transcripts and protein in the adult cycling ovary.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The expression profiles of MIS in the adult human and monkey ovary are identical and comparable to that observed previously in other species (Bezard et al 1987, Uneo et al 1989a, Baarends et al 1995, Juengel et al 2002, Visser et al 2006. Table 1 compares the results of different studies on cellular localization of MIS transcripts and protein in the adult cycling ovary.…”
Section: Discussionsupporting
confidence: 59%
“…While in this study and that reported by Stubbs et al (2005), MIS is detected in the granulosa cells of primordial follicles until ovulatory follicles; weak, but specific MIS transcripts and protein are detectable in the stromal cells. Contrasting these observations, previous studies have reported the absence of MIS in the primordial follicles and stroma (Bezard et al 1987, Uneo et al 1989a, Baarends et al 1995, Juengel et al 2002. To our knowledge, granulosa cells of the primordial follicles and the ovarian stroma as sites of MIS synthesis have not been reported earlier.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Expression of AMH increases as the follicle develops through the preantral and small antral stages in humans (Weenen et al 2004). Similar patterns occur in non-human primates (Modi et al 2006), mice (Gruijters et al 2003), rats (Ueno et al 1989, Hirobe et al 1994, Baarends et al 1995, Siberian hamsters (Shahed & Young 2013), cows (Monniaux et al 2012), goats (Monniaux et al 2012, Rocha et al 2016, sheep (Bezard et al 1987) and brushtail possums (Juengel et al 2002). AMH expression declines as follicles progress through the large antral stage of folliculogenesis, with little AMH being produced in preovulatory follicles (Ueno et al 1989, Weenen et al 2004, Jeppesen et al 2013.…”
Section: Anti-müllerian Hormone Expression In the Ovarymentioning
confidence: 65%
“…AMH is synthesised in the gonads of all vertebrate species examined to date, including fish (Western et al 1999, Halm et al 2007, amphibians (Kodama et al 2015), birds (Smith et al 1999, Nishikimi et al 2000, reptiles (Western et al 1999, Shoemaker et al 2007, marsupials (Juengel et al 2002, Pask et al 2004 and eutherian mammals (Josso 1973, Meyers-Wallen et al 1987, Kuroda et al 1990. In fish that do not have Müllerian ducts, AMH regulates the proliferation of germ cells in both sexes (Morinaga et al 2007).…”
Section: Amh Is a Gonadal Cytokinementioning
confidence: 99%